Graph translation

HideShow resource information

y=f(x+c)

Translation horizontally in the opposite direction of the sighn

e.g y=f(x+3) whould be 3 to the left


1 of 6

y=f(x)+c

y=f(x)+c 

Translation in the vertical component and it is how you think it would be 

E.g y=f(x)+4  would raise by 4 in the y co-ords

2 of 6

y=f(kx)

y=f(kx)

Stretch in the horizontal axis, you would do:               

(1÷ k)   X   (x co-ord)

 


3 of 6

y=KF(X)

y=KF(X)  Vertical Stretch

= (X, KY)

4 of 6

Y= -F(X)

Y= -F(X) Reflection in X axis 

(X,-Y)

5 of 6

Y=F(-X)

Y=F(-X) Translation in the Y axis 

(-X, Y)

6 of 6

Comments

No comments have yet been made

Similar Mathematics resources:

See all Mathematics resources »See all Graphs and transformations resources »